Aperture Synthesis Shows Perceptual Integration of Geometrical Form Across Saccades. (March 2018) - Schreiber, Kai; Morgan, Michael
We investigated the perceptual bias in perceived relative lengths in the Brentano version of the Müller-Lyer arrowheads figure. The magnitude of the bias was measured both under normal whole-figure viewing condition and under an aperture viewing condition, where participants moved their gaze around the figure but could see only one arrowhead at a time through a Gaussian-weighted contrast window. The extent of the perceptual bias was similar under the two conditions. The stimuli were presented on a CRT in a light-proof room with room-lights off, but visual context was provided by a rectangular frame surrounding the figure. The frame was either stationary with respect to the figure or moved in such a manner that the bias would be counteracted if the observer were locating features with respect to the frame. Biases were reduced in the latter condition. We conclude that integration occurs over saccades, but largely in an external visual framework, rather than in a body-centered frame using an extraretinal signal.